Rapid response to single agent daratumumab is associated with improved progression-free survival in relapsed/refractory AL amyloidosis. (2nd July 2020) - Cohen, Oliver C.; Brodermann, Maximillian H.; Blakeney, Iona J.; Mahmood, Shameem; Sachchithanantham, Sajitha; Ravichandran, Sriram; Law, Steven; Lachmann, Helen J.; Whelan, Carol J.; Popat, Rakesh; Rabin, Neil; Yong, Kwee; et al.
Abstract: Background: Daratumumab is a monoclonal antibody, which targets CD38; an antigen expressed on malignant plasma cells in AL amyloidosis thus providing a rationale for its use. Method: Patients treated with daratumumab monotherapy (2016–2019) for relapsed/refractory systemic AL amyloidosis were identified from the database at the UK National Amyloidosis Centre. Results: Of 50 evaluable patients, haematological responses at 3 months were: CR – 19 (38%), VGPR – 14 (28%), PR – 9 (18%) and no response – 8 (16%). Median time to response was 1 (1–6) month. Of assessable patients, cardiac, renal and hepatic responses were seen in 43.8%, 25.0% and 0% of patients whilst progression occurred in 25.0%, 12.5% and 37.5% respectively. Patients achieving a CR had longer median OS (not reached vs. 22.7 months [95% CI 17.0–28.4 months]) ( p  = .036). Furthermore, patients achieving a rapid response (at 1 month) had a longer median PFS (not reached vs. 9 months [95% CI 5.8–12.2 months]) ( p  = .013). Conclusion: Daratumumab monotherapy is effective in multiply-relapsed systemic AL amyloidosis and should be considered, if available, in patients who have not received prior daratumumab therapy. Responses are achieved rapidly and overall response rate was 84%. CR predicts overall survival whilst speed of response is predictive of a longer PFS.